Comparative analyses of locally developed and imported votex rice thresher - Dauda, S. M.; Dzivama, A. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
The efforts to discover and make optimal and effective use of locally developed rice thresher as substitute for imported rice threshers form the focus of this paper. A locally developed rice thresher was compared with an imported Votex rice fan from Holland.  The study was based on threshing efficiency, cleaning efficiency, total grain losses, grain recovery range, capacity utilization and threshing intensity. Three popular rice varieties, Faro 51, Faro 29 and Faro 21 were used to evaluate the performances of the threshers. The results showed that, the local thresher had 98.01%, 99.32%, 4.78%, 95.22%, 54.67% and 0.029 kWkg-1, as: threshing efficiency, cleaning efficiency, total grain loss, grain recovery range, and capacity utilization and threshing intensity respectively. Whereas the imported votex rice fan thresher had 98%, 95.77%, 8.72%, 91.28%, 76.97% and0.0037 kWkg-1 as threshing efficiency, cleaning efficiency, total grain loss, grain recovery range, capacity utilization and threshing intensity respectively. Thus the local thresher compared favorably with the imported thresher and can be used as substituted thereby conserving Nigeria’s foreign exchange.